Designing a dual-wavelength excitation Eu3+/Mn4+ co-doped phosphors for high-sensitivity luminescence thermometry. Issue 12 (15th June 2023) - Shi, Xinyang; Chen, Yuqi; Li, Guixian; Qiang, Kangrui; Mao, Qinan; Pei, Lang; Liu, Meijiao; Zhong, Jiasong
Abstract: Luminescence thermometry has been widely concerned by researchers due to its quick response, high spatial resolution, and remote measurement. However, low sensitivity is still an existing problem and affects its development. Herein, the luminescence thermometer with high sensitivity taking advantage of the distinguished thermal response between Eu 3+ and Mn 4+ is designed. Excitedly, Eu 3+ exhibits an anti-thermal quenching behavior under 310 nm excitation and a slight thermal quenching behavior under 393 nm excitation due to the energy transfer of host→Eu 3+, while Mn 4+ presents a strong thermal quenching behavior. Moreover, the energy transfer of Eu 3+ →Mn 4+ (λex  = 310 nm and λex  = 393 nm) can also be observed for the Ca2 Sb2 O7 : Eu 3+, Mn 4+ phosphors during the heating process. On the basis of the diverse thermal quenching behavior of Eu 3+ and Mn 4+, the thermometric performances are investigated by utilizing the fluorescence intensity ratio (FIR) of Eu 3+ ( 5 D0 → 7 F2 )/Mn 4+ ( 2 Eg → 4 A2g ) under a dual-wavelength excitation. The maximum relative sensitivities of the designed phosphors are determined to be 4.072% K −1 at 305 K under 310 nm and 3.072% K −1 at 351 K under 393 nm excitation. It's worth noting that the thermometric characteristic can be modified by various excitation wavelengths. Hence, the developed Ca2 Sb2 O7 : Eu 3+, Mn 4+ phosphors have great potential in the field of luminescence thermometry and provide an effective strategy for designing high-sensitivity dual-wavelength excitation optical thermometers. Graphical abstract: Image 1